Ipilimumab therapy in patients with advanced melanoma and preexisting autoimmune disorders - Johnson, Douglas B.; Bender, Carolin; Hassel, Jessica C. (JAMA oncology, 2016)
Importance Ipilimumab and other immune therapies are effective treatment options for patients with advanced melanoma but cause frequent immune-related toxic effects. Autoimmune diseases are common, and the safety and efficacy of ipilimumab therapy in patients with preexisting autoimmune disorders is not known. Objective To determine the safety and efficacy of ipilimumab therapy in patients with advanced melanoma with preexisting autoimmune disorders. Design, Setting, and Participants Retrospective review of patients with advanced melanoma and preexisting autoimmune disorders who received ipilimumab at 9 academic tertiary referral centers from January 1, 2012, through August 1, 2015. The data analysis was performed on August 24, 2015. Exposure Ipilimumab therapy. Main Outcomes and Measures Safety, in terms of frequency of autoimmune flares and conventional immune-related adverse events (irAEs), and efficacy, in terms of response rates and overall survival, were evaluated descriptively. Results Of the 30 patients who received ipilimumab (17 [57%] male; median [range] age, 59.5 [30-80] y), 6 had rheumatoid arthritis, 5 had psoriasis, 6 had inflammatory bowel disease, 2 had systemic lupus erythematosus, 2 had multiple sclerosis, 2 had autoimmune thyroiditis, and 7 had other conditions. Thirteen patients (43%) were receiving immunosuppressive therapy at the time of initiation of ipilimumab therapy, most commonly low-dose prednisone or hydroxychloroquine. With ipilimumab treatment, 8 patients (27%) experienced exacerbations of their autoimmune condition necessitating systemic treatment; all were managed with corticosteroids. Conventional grade 3 to 5 irAEs occurred in 10 patients (33%) and were reversible with corticosteroids or with infliximab therapy in 2 cases. One patient with baseline psoriasis died of presumed immune-related colitis after a 1-week delay prior to reporting symptoms. Fifteen patients (50%) had neither autoimmune disease flares nor irAEs. Six patients experienced an objective response (20%), including 1 with a durable complete response. Conclusions and Relevance To our knowledge, this is the largest series of patients with preexisting autoimmune disease treated with immune checkpoint inhibitors. Ipilimumab was clinically active and was associated with exacerbations of autoimmune disease and conventional ipilimumab-induced irAEs that were readily manageable with standard therapies when started in a timely fashion. Ipilimumab therapy may be considered in this setting with vigilant clinical monitoring.